Mucormycosis at pectoralis major myocutaneous flap donor site - Saraiya Hemant; Tankshali Rajen (Indian Journal of Plastic Surgery)
Background: Advanced carcinomas involving the head and neck present a major therapeutic challenge because of their poor prognosis particularly in old age irrespective of the treatment modality used. Materials and Methods: A 71-year-old patient presented with right-sided buccal mucosal carcinoma involving the mandible. Composite resection with removal of mandible and radical neck dissection was done. Pectoralis major myocutaneous flap (PMMC) with deltopectoral flap was done to cover the defect. On the 14th day mucormycosis was noted on pectoralis major myocutaneous flap donor site. Radical debridement and appropriate antibiotic and antifungal treatment was started. The patient was put on life support system. Results: Despite aggressive treatment the patient died. Conclusion: This case reaffirms the views that radical surgical procedure should be carried out with caution in old patients with preexisting diseases as the chances of life-threatening complications are very high in these patients. Mucormycosis at pectoralis major myocutaneous flap (PMMC) donor site is probably being reported for the first time.